Implementing adaptive management: A front-line effort — Is there an emerging practice? - Teskey, Graham; Tyrrel, Lavinia (Working Paper, 2021)
Among the many principles that currently inform donor-funded development initiatives, three appear to stand out: they should be politically informed, locally led, and adaptive. There is as yet little practical guidance for aid implementers regarding how to operationalise these approaches. What will it take to shift practice away from linear and planned approaches, towards models which foster local leadership and which engage with emergent and complex systems? This paper suggests that the answer is not to throw out the discipline of the logical framework, results frameworks, or theories of change. Rather they need to be handled rather more reflectively and ‘elastically’. The purpose of this paper is to set out how this can be achieved, and to propose 15 tools for donors, implementors and front-line staff to apply adaptive management (AM) in practice, at critical stages of the project cycle and within the dominant aid paradigm. This is what we are calling PILLAR: politically informed, locally led and adaptive responses. We are framing PILLAR to cover the full project cycle (design, implementation and review), hence the nomenclature of an ‘end to end’ approach. Our hope is that these tools will eventually replace the current planned, log-frame driven and top-down approach to aid design and delivery which dominates the development sector.

Value for money and adaptive programming - Approaches, measures and management - Laws, Ed; Valters, Craig (ODI, 2021)
- The United Kingdom’s Foreign, Commonwealth and Development Office (FCDO)’s standard economy, efficiency, effectiveness/cost-effectiveness and equity (4E) framework is still relevant for approaching, measuring and managing value for money (VfM) for adaptive programmes. • However, this framework needs to be reframed to capture and incentivise flexibility, learning and adaptation. • VfM appraisal and reporting should be done in a way that draws on beneficiary feedback and informs good decision-making, rather than just being a compliance exercise. • If VfM appraisal and reporting cannot be done appropriately for adaptive programmes, it should be avoided or minimised. There is a risk of diverting time and resources from more suitable tools and methods.

Opportunities and challenges for DAC members in ‘adapting to context’ - Sharp, Samuel; Wild, Leni (2021)
Key Messages New principles for OECD DAC members on ‘Managing for Sustainable Development Results’ emphasise tailoring result management approaches to different contexts; balancing internal compliance with empowerment at ground level; and adapting implementation in the pursuit of long-term outcomes. However development organisations face numerous challenges in aligning with these principles in practice. Reporting and evidence collection processes do not consistently encourage adaptive practice, reflecting their orientation towards accountability over learning. Context analysis is common during programme design, but used less on an ongoing basis. Popular tools –such as logical frameworks and theories of change - are often intepreted in linear ways, not as ‘living documents’ that react and change over time. Organisations need to meaningfully empower staff to work adaptively, including examining incentives and cultures that can make staff more comfortable with traditional results management. Even when senior leadership is supportive of adaptive ways of working, they can lack a clear understanding of the resourcing required and appropriate governance and management processes. Development organisations and their partners have attempted to address these challenges through the use of different monitoring and evaluation tools and methods, changes to reporting frameworks and templates, and initiatives to create positive incentives and motivate staff, leadership and partners at different levels.
Keywords: _tablet

LearnAdapt: a synthesis of our work on adaptive programming with DFID/FCDO (2017–2020) - Laws, Ed; Pett, Jamie; Proud, Emma; Rocha Menocal, Alina (Briefing Note, 2021)
Key takeaways. • Development is not linear or straightforward, but rather complex, uncertain and context-specific. This calls for international development actors to work differently, in ways that are based on deliberate experimentation, learning and adaptation, to inform decisions and drive effective development. • Although it might go by different names, adaptive programming has been used in a variety of areas and fields in both the public and private sectors. Development practitioners have much to learn from and contribute to these different approaches and experiences. • Trust and relationship-building across all relevant stakeholders are among the most critical enabling factors for adaptive management. They are essential to give partners the space, autonomy and authority needed to try, test, reflect, iterate and feed back at the frontline of implementation, and to give donors the confidence that decisions are being made on the basis of evidence and learning to improve effectiveness. • There is an urgent need to rethink how accountability requirements, results frameworks, value for money considerations, performance markers, procurement and contracting mechanisms and other processes are understood and applied so that they are better aligned with and can support adaptive management more effectively. • The role of senior managers leading adaptive programmes from the donor side should be to create a space for experimentation and learning. Funders should hold their partners accountable for learning and how it feeds into effective programming, rather than for delivering on predetermined targets. • While formal guidance is important, leadership, champions, institutional incentives, a supportive management culture and appropriate mindsets are essential to encourage adaptive ways of working. • Adaptive management is resource-intensive. It requires skill, commitment, time for building trust and investments in learning. It is a journey, not an immediate destination – so it calls for patience, open-mindedness and a more nuanced approach to risk.

Learning to adapt & adapting to learn - Using elements of outcome mapping in the ‘Resilient Adolescents in the Syria Crisis’ programme - van Ongevalle, Jan; Kvintradze, Ana; Rennesson, Gaël; Miller, David (Save the Children, 2021)
This learning paper highlights how elements of outcome mapping were used by Save the Children Sweden in a project (2018-2020) that supports adolescents, affected by the Syria crisis, to become more resilient. The paper first outlines how the spheres of influence framework has been applied to develop an actor focused theory of change. It then describes how progress markers, as an alternative to SMART indicators, were formulated to monitor the programme’s results. The paper also outlines how long lists of progress markers were categorised in a more realistic and practical results framework. The paper then continues to elaborate how outcome journals, qualitative data analysis techniques and regular review meetings and reflection workshops were utilised for data collection, for collective learning among programme stakeholders and for informing planning and programme adjustment. Various practical guidelines and tips on how to implement elements of outcome mapping are provided. The final part of the paper explores to what extent outcome mapping was able to foster several key enablers of adaptive programme management and highlights some of the challenges that programme stakeholders faced. Practical recommendations towards the use of outcome mapping in future programmes are also proposed.